2014
DOI: 10.1016/j.ijcard.2014.03.168
|View full text |Cite
|
Sign up to set email alerts
|

Association of myeloperoxidase with total and cardiovascular mortality in individuals undergoing coronary angiography—The LURIC study

Abstract: BackgroundThe phagocytic enzyme myeloperoxidase (MPO) acts as a front-line defender against microorganisms. However, increased MPO levels have been found to be associated with complex and calcified atherosclerotic lesions and incident cardiovascular disease. Therefore, this study aimed to investigate a predictive role of MPO, a biomarker of inflammation and oxidative stress, for total and cardiovascular mortality in patients referred to coronary angiography.Methods and resultsMPO plasma concentrations along wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 51 publications
1
19
0
5
Order By: Relevance
“…After 13 years follow-up and covariate analysis, patients with the highest MPO tertile were twice as likely to have died from a cardiovascular event than those in the lowest tertile [98]. In patients with angiographic CAD followed for nearly 8 years, those in the highest MPO quartile were 1.5 times more likely to die from cardiovascular causes than those in the lowest MPO quartile after fully adjusting for variables [105]. Interestingly, a separate study using a follow-up of only 3.5 years did not observe MPO to independently correlate with mortality in patients with stable CAD [118].…”
Section: Evidence For Mpo Predicting Cardiovascular Mortalitymentioning
confidence: 94%
See 2 more Smart Citations
“…After 13 years follow-up and covariate analysis, patients with the highest MPO tertile were twice as likely to have died from a cardiovascular event than those in the lowest tertile [98]. In patients with angiographic CAD followed for nearly 8 years, those in the highest MPO quartile were 1.5 times more likely to die from cardiovascular causes than those in the lowest MPO quartile after fully adjusting for variables [105]. Interestingly, a separate study using a follow-up of only 3.5 years did not observe MPO to independently correlate with mortality in patients with stable CAD [118].…”
Section: Evidence For Mpo Predicting Cardiovascular Mortalitymentioning
confidence: 94%
“…This suggests that systemic release of MPO is not a characteristic feature of asymptomatic CAD, although a possible confounding factor in one of these two studies is that the absence of CAD in the control group of volunteers was not ruled out angiographically [102]. Two other studies reporting a lack of significant association between MPO and CAD [104,105] used unusual definitions of disease severity. Specifically, in a study consisting of 3036 patients hospitalized for coronary angiography, CAD was diagnosed as >20% stenosis [105] rather than the 50% benchmark considered to be relevant for CAD outcome [106].…”
Section: Evidence For Association Between Circulating Mpo and Cadmentioning
confidence: 99%
See 1 more Smart Citation
“…Another possible mechanism responsible for this phenomenon is polymorphism in the promoter region of the MPO gene. Several genetic polymorphisms in the MPO gene were described (Wainstein et al, 2010;Scharnagi et al, 2014;Nikpoor et al, 2001). Some studies suggest that MPO polymorphism in the promoter region (-463G/A) might be associated with coronary artery disease (Castellani et al, 2006;Reynolds et al, 2006;Yang et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study indicated that MPO does not hold any role in the progression of cardiovascular conditions but, it indicated a good correlation between MPO concentrations, and cardiovascular and all-cause death rates. 10 In another prospective study, a significant association was demonstrated between MPO levels, heart-type fatty acid-binding protein (H-FABP) and troponin T (TnT) levels as markers of myocardial damage in HF patients. The results showed that MPO could have a say in the development and progression of myocardial injury in cases with CHF, even if MPO levels were not associated with TnT levels.…”
Section: Myeloperoxidasementioning
confidence: 99%